2011
DOI: 10.1161/circresaha.110.239665
|View full text |Cite
|
Sign up to set email alerts
|

Local Retention Versus Systemic Release of Soluble VEGF Receptor-1 Are Mediated by Heparin-Binding and Regulated by Heparanase

Abstract: Rationale:The vascular endothelial growth factor (VEGF) decoy receptor soluble VEGF-R1 (sVEGF-R1) is thought to protect the cells that produce it from adverse VEGF signaling. To accomplish this role, a mechanism for pericellular retention of sVEGF-R1 is required. Local retention may also prevent the accumulation of high circulating levels of sVEGF-R1 and resulting interference with homeostatic VEGF functions in remote organs.Objective: To reveal natural storage depots of sVEGF-R1 and determine mechanisms under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
79
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 25 publications
13
79
1
Order By: Relevance
“…76 Because sFlt-1 binds to the cell surface or extracellular matrix via heparan sulfate proteoglycans, LMWH may displace sFlt-1 from these heparin-binding sites via competitive binding, leading to higher levels of sFlt-1 while yielding an improvement in endothelial function. 74 This proposed mechanism would be consistent with previous reports that heparin increases the bioavailability of NO in patients with coronary artery disease, whereas concurrently increasing levels of circulating MPO. 58 Levels of circulating MPO are also elevated in PE, with both sFlt-1 and MPO bound to the endothelium via heparan sulfate proteoglycans and displaced by LMWH.…”
Section: Effects Of Lmwh On Circulating Levels Of Angiogenic Proteinssupporting
confidence: 90%
See 2 more Smart Citations
“…76 Because sFlt-1 binds to the cell surface or extracellular matrix via heparan sulfate proteoglycans, LMWH may displace sFlt-1 from these heparin-binding sites via competitive binding, leading to higher levels of sFlt-1 while yielding an improvement in endothelial function. 74 This proposed mechanism would be consistent with previous reports that heparin increases the bioavailability of NO in patients with coronary artery disease, whereas concurrently increasing levels of circulating MPO. 58 Levels of circulating MPO are also elevated in PE, with both sFlt-1 and MPO bound to the endothelium via heparan sulfate proteoglycans and displaced by LMWH.…”
Section: Effects Of Lmwh On Circulating Levels Of Angiogenic Proteinssupporting
confidence: 90%
“…Clinical and animal studies have determined that the LMWH administration significantly increases serum levels of sFlt-1. 52,73,74 Although large, these heparin-induced elevations in circulating sFlt-1 are likely not pathogenic because women who require heparin anticoagulation throughout pregnancy do not seem to have an increased risk of developing PE. 75 In functional terms, endothelium-bound sFlt-1 becomes available for enhanced renal excretion because of mobilization by circulating heparin.…”
Section: Effects Of Lmwh On Circulating Levels Of Angiogenic Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…71 sFlt1 is locally retained on the surface of placental villi, where it can be released via the heparanase action of LMWH. 70,72 Interestingly, LMWH induces transcription and translation of sFlt1 in floating first-trimester villous explants, further contributing to the LMWH-induced secretion in a manner that antagonizes VEGF receptor phosphorylation. 73 This disparity in clinical and in vitro observations suggests more complex interactions between the placenta and LMWH to mediate a preventive role of heparin in women at high risk of severe PE.…”
Section: Pathogenesis Of Severe Pementioning
confidence: 99%
“…We demonstrated that both unfractionated heparin (UFH) and LMWH, in comparable doses used clinically in pregnancy, are capable of reversing the natural antiangiogenic tendency of first-trimester placental villi. 97 These heparins exert this proangiogenic effect despite increasing secretion of sFLT1 70,72 that at least in vitro impairs VEGF receptor signaling. 75 This paradox between in vitro and in vivo data in the context of sFLT1 may be because of the restoration additional functions of the outer syncytiotrophoblast that override the endothelial-specific effects of excess sFLT1.…”
Section: Heparin For Prevention Of Obstetric Complications 4783 Bloodmentioning
confidence: 99%